Neutral Complexes of Alkali Metals with 5,7-Substituted Oximes - Prakash, Dharm; Pd. Roy, Amarendra; Prakash Gupta, Om (Asian Journal of Chemistry, 2012)
Complexes of alkali metal with 5,7-dinitro-oxine, 5,7-dichlorooxine and 5,7-dibromo-oxine have been synthesized and characterized on the basis of physico-chemical data. The IR spectra data indicate that the ligands are coordinated to the metal atom via hydroxyl oxygen and ‘N’ atom of the quinoline ring. It also indicates the presence of hydrogen bonding in them, which may be one of the dominant factors for the stability of these complexes.